2023
DOI: 10.1007/s10652-023-09920-6
|View full text |Cite|
|
Sign up to set email alerts
|

Oceanic bottom mixed layer in the Clarion-Clipperton Zone: potential influence on deep-seabed mining plume dispersal

Abstract: The oceanic bottom mixed layer (BML) is a well mixed, weakly stratified, turbulent boundary layer. Adjacent to the seabed, the BML is of intrinsic importance for studying ocean mixing, energy dissipation, particle cycling and sediment-water interactions. While deep-seabed mining of polymetallic nodules is anticipated to commence in the Clarion-Clipperton Zone (CCZ) of the northeastern tropical Pacific Ocean, knowledge gaps regarding the form of the BML and its potentially key influence on the dispersal of sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…generate benthic plumes of sediment, and other biogeochemical factors (e.g., dissolved heavy metals), that have the potential to negatively impact the ocean environment (Peacock and Ouillon, 2023). Recent modeling studies identified turbulent vertical mixing as a critical parameter that influences model predictions of plume extent, which will be the basis of decision-making by regulators (Chen et al, 2023).…”
Section: Turbulent Fluxes Factor Into Natural Resource Assessmentsmentioning
confidence: 99%
“…generate benthic plumes of sediment, and other biogeochemical factors (e.g., dissolved heavy metals), that have the potential to negatively impact the ocean environment (Peacock and Ouillon, 2023). Recent modeling studies identified turbulent vertical mixing as a critical parameter that influences model predictions of plume extent, which will be the basis of decision-making by regulators (Chen et al, 2023).…”
Section: Turbulent Fluxes Factor Into Natural Resource Assessmentsmentioning
confidence: 99%
“…However, there is no evidence showing that benthic storms mix sediment to depths greater than 20 cm (DeMaster et al., 1985; Volz et al., 2020). Observational records indicate that benthic storms and sediment resuspension events, due to abyssal benthic flows, are relatively weak in the manganese nodule zone compared with other places around the world ocean (Chen et al., 2023). Bottom current speeds measured over nodule fields are too low (<5 cm s −1 ) to erode sediments (Dutkiewicz et al., 2020), indicating that the enhanced sediment mixing, observed in the CCZ during the post exploration period, was not caused by natural ocean dynamic processes, further supporting evidence for anthropogenic disturb.…”
Section: Resultsmentioning
confidence: 99%
“…With rising interests in deep‐sea mining and marine carbon dioxide removal (S.‐Y. S. Chen et al., 2023; Miller et al., 2018; Peacock & Ouillon, 2023; Ryabinin et al., 2019), there is also a pressing need to understand transient motions in the deep ocean.…”
Section: Introductionmentioning
confidence: 99%